Inadequate Preoperative Team Briefings Lead to More Intraoperative Adverse Events. Issue 2 (June 2018) - Phadnis, Joideep; Templeton-Ward, Oliver
Abstract : Introduction: Implementation of the World Health Organization checklists has reduced major surgical complications and errors; however, the impact of preoperative briefings on intraoperative adverse events has not been assessed. Materials and Methods: A prospective case-control study assessing the association between preoperative briefings and minor, potentially major, and major adverse intraoperative events was performed in 2 phases. Phase 1 involved prospective data collection for all trauma and orthopedic lists during a 2-week period. Changes were implemented as a result of the findings, and after this, the study was repeated (phase 2) to assess for the effect of the changes made to the practice. Results: Forty-one lists were audited during phase 1 and 47 lists were audited during phase 2 of the study. Adequate preoperative briefings were performed in 10 (24%) of 41 lists in phase 1. There was a significant association between the occurrences of intraoperative adverse events (n = 37) when a briefing was not performed ( P = < 0.01) and when a briefing was performed incompletely ( P = 0.01). In phase 2, after staff reeducation and policy change, briefings were found to be adequate in 38 (81%) of 47 lists with the occurrence of only 3 adverse events. Team familiarity also improved significantly as a result of better preoperative briefings ( P = 0.02). Conclusions: Inadequate preoperative briefings are associated with an increase in minor adverse events and are detrimental to team familiarity. On the basis of our findings, we recommend that all surgical units perform preoperative briefings thoroughly to minimize these factors.